MERAWAT HAFALAN AL-QUR’AN BAGI YANG SUDAH MENIKAH DI ERA GLOBALISASI - Simanjuntak, Dahliati (Al FAWATIH:Jurnal Kajian Al Quran dan Hadis, 2025)
A hadith states that memorizing the Koran quickly disappears from memory. Besides that, there is a hadith about the threat to those who forget to memorize the Koran. Based on this reality, the author will examine what kind of efforts are made to maintain memorization because the situation is different from before. At first they live in an environment that supports the process of memorizing and maintaining memorization. In contrast to today's era, supportive conditions are needed to maintain the memorization of the Koran. This is related to the many obstacles faced by hafizh/hafizhah in maintaining their memorization, such as the hustle and bustle of life, globalization, busyness in the family and personal busyness. They are also like humans in general who have the necessities of life. This research aims to describe how efforts are made to preserve the memorization of the Koran so that it remains in their memory as a great and special charity. This type of research is field research. The research instruments are observation, interview guidelines. The data source for this research is the results of interviews obtained from hafidz/dzah who are married in Panyabungan Mandailing Natal. As for the results of this research, the means of maintaining memorization of the Koran carried out by huffazh in Panyabungan is through two efforts, namely physical and mental. These include making the Koran delicious (read after prayer), muraja'ah (nderes) in between daily activities such as cooking and other activities, discipline and istiqamah with the target of memorizing, teaching the Koran (accepting students' memorization deposits), participating Sima'an actively participates in various community events. Inner efforts such as fasting, maintaining the habit of al-wudhu' (always in a pure/pure state), avoiding sin, praying day and night and prayer. Factors that help hafidz-hafidzah in maintaining memory: Strong belief in the hafidz/dzah in the glory promised by Allah to those who study and teach the Koran, belief in the need to remember and fear of sin by forgetting it, support and understanding from most people/family, relatives, attendance at sima'an and Al-Quran study. In particular, hafidz/dzah do not find it difficult to remember. According to them, taking care of memorization is up to each person. If there is a discipline that can maintain consistency, anyone can do it.